Reduction of Endothelial Nitric Oxide Increases the Adhesiveness of Constitutive Endothelial Membrane ICAM-1 through Src-Mediated Phosphorylation - Gao, Feng; Lucke-Wold, Brandon P.; Li, Xiang; Logsdon, Aric F.; Xu, Li-Chong; Xu, Sulei; LaPenna, Kyle B.; Wang, Huaqi; Talukder, M. A. Hassan; Siedlecki, Christopher A.; Huber, Jason D.; Rosen, Charles L.; et al. (Frontiers in Physiology, 2018)
Nitric oxide (NO) is a known anti-adhesive molecule that prevents platelet aggregation and leukocyte adhesion to endothelial cells (ECs). The mechanism has been attributed to its role in the regulation of adhesion molecules on leukocytes and the adhesive properties of platelets. Our previous study conducted in rat venules found that reduction of EC basal NO synthesis caused EC ICAM-1-mediated firm adhesion of leukocytes within 10-30 minutes. This quick response occurred in the absence of alterations of adhesion molecules on leukocytes and also opposes the classical pattern of ICAM-1-mediated leukocyte adhesion that requires protein synthesis and occurs hours after stimulation. The objective of this study is to investigate the underlying mechanisms of reduced basal NO-induced EC-mediated rapid leukocyte adhesion observed in intact microvessels. The relative levels of ICAM-1 at different cell regions and their activation status were determined with cellular fractionation and western blot using cultured human umbilical vein ECs. ICAM-1 adhesiveness was determined by immunoprecipitation in non-denatured proteins to assess the changes in ICAM-1 binding to its inhibitory antibody, mAb1A29, and antibody against total ICAM-1 with and without NO reduction. The adhesion strength of EC ICAM-1 was assessed by atomic force microscopy (AFM) on live cells. Results showed that reduction of EC basal NO caused by the application of caveolin-1 scaffolding domain (AP-CAV) or NOS inhibitor, L-NMMA, for 30 min significantly increased phosphorylated ICAM-1 and its binding to mAb1A29 in the absence of altered ICAM-1 expression and its distribution at subcellular regions. The Src inhibitor, PP1, inhibited NO reduction-induced increases in ICAM-1 phosphorylation and adhesive binding. AFM detected significant increases in the binding force between AP-CAV-treated ECs and mAb1A29-coated probes. These results demonstrated that reduced EC basal NO lead to a rapid increase in ICAM-1 adhesive binding via Src-mediated phosphorylation without de novo protein synthesis and translocation. This study suggests that a NO-dependent conformational change of constitutive EC membrane ICAM-1 might be the mechanism of rapid ICAM-1 dependent leukocyte adhesion observed in vivo. This new mechanistic insight provides a better understanding of EC/leukocyte interaction-mediated vascular inflammation under many disease conditions that encounter reduced basal NO in the circulation system.